SURVEY PENGETAHUAN TENTANG PENCEGAHAN COVID-19 PADA MAHASISWA UNIVERSITAS CITRA BANGSA KUPANG - Elizeu Dos Santos Da Silva; Analizza Ina Lea; Erna Febriyanti (CHMK HEALTH JOURNAL, 2021)
Corona Virus Disease (Covid-19) becomes a serious problem across the world nowadays due to it could cause death for the community and health workers, hence it becomes a priority of the service to both global health and nation. Knowledge of the student against the pandemic of Covid-19 are significant to reduce the Covid-19 transmission. This research is aimed to describe the knowledge on Covid-19 prevention to the Student of Citra Bangsa Kupang University. This research used a quantitative research design with a descriptive survey approach. The sample collected consists of 144 respondents of the student at the Citra Bangsa University of Kupang by using a cluster sampling technique. The technique of analyzing data used was a univariate analysis technique with the frequency of distribution variable. The instrument used as a tool of analysis data was a questionnaire shared through a google form. The results of the analysis showed that of the knowledge student against Covid-19 prevention are; total of 97 respondents (67.4%) of student have good knowledge of Covid-19 preventions. The student of the Citra Bangsa University of Kupang is expected to health protocol and continue enhancing knowledge to face the pandemic of Covid-19, to reduce the risk of COVID-19 transmission. Keywords: Knowledge, Covid-19.